Leaving, Staying, or Coming Back? : Migration Decisions during the Northern Mali Conflict - Hoogeveen, Johannes G.; Rossi, Mariacristina; Sansone, Dario (World Bank, Washington, DC, 2017)
This paper uses a unique data set to analyze the migration dynamics of refugees, returnees, and internally displaced people during the Northern Mali conflict. Individuals were interviewed monthly using mobile phones. The results cast light on the characteristics of these three groups before and after the crisis. In addition, the paper tests how employment status, security, and expectations affect people's willingness to go back home. The findings suggest that the decision to return is affected by a comparison of (opportunity) costs and benefits, but also by other factors. Individuals who are employed while displaced are less willing to go back to the North, as are better educated individuals or those receiving assistance. The opposite is true for those whose ethnicity is Songhai, as well as for those who originated from Kidal. The results show that higher educated individuals performed better when displaced and in case they decide to return, they find a job more easily.